Eco Friendly Machining Processes for Sustainability - Review. Issue 1 (October 2020) - Rajmohan, T.; Kalyan Chakravarthy, V.V.; Nandakumar, A.; Satish Kumar, S.D.
Abstract: Green manufacturing is a style for industrialized that minimizes dissipate and contamination. The pollution prevention resolves in manufacturing industries to expand and execute various environmentally-friendly strategies. The main purpose of green machining is to hold up future generations by attaining sustainability. Cutting fluids are discoloured with metal particles and foulness products which reduce the efficiency of cutting fluids. To minimize the unpleasant environmental effects coupled with the use of cutting fluids, the harmful components from their formulations have to be eliminated or reduced to the acceptable level. In addition, mineral based cutting fluids are going to be replaced with vegetable based cutting fluids since they are environmentally friendly. The present review primarily determined on examining different aspects of machining process from an environmental sensitivity. This paper presents the environmental green machining such as dry machining, machining with minimum quantity lubricant, Cryogenic machining, hot machining, vegetable oil-based cutting fluids and nano filled cutting fluids. The Performance of Eco-friendly machining are discussed in terms of cutting forces, tool flank wear, cutting temperatures and surface finish are also discussed.